Criminal Responsibility on Captain of Commersial Vessel by Act No 17 of 2008 on Voyage - Subekhan Subekhan; Lathifah Hanim (Jurnal Daulat Hukum, 2020)
The cruise is one of the nation's transportation system that has a strategic importance and as a liaison and outreach throughout the territory of Indonesia's sovereignty and the potential beneficial role for society, both nationally and internationally. The problems of this study are: 1) Why the skipper commercial vessels should be responsible in case of Vesselwreck, 2) How does the skipper criminal liability due to accidents aboard commercial vessels according to Act No. 17 Of 2008 On Voyage? 3) Is it possible corporate criminal liability in accidents merchant vessel according to Act No. 17 Of 2008 On Voyage?Researchers used the method is legal normative juridical approach and specification in this study were included descriptive analysis.  Sources and types of data in this research is secondary data obtained from the study of literature. Data were analyzed qualitatively. The problems studied by the theory of legal certainty and criminal liability.Based on the results of research that skipper as a leader on the Vessel, is fully responsible for the safety of the Vessel, passengers and cargo during the voyage from the port of loading to the port of destination. Criminal sanctions needed to enforce these responsibilities, and sanctions that have been regulated in Act No. 17 Of 2008 on Voyage Article 244 paragraph (3) and (4), 20 Article 247 and Article 248 shall be punished with imprisonment beyond three (3) years or a fine of Rp 400.000.000.00, - (four hundred million). Obliged to take countermeasures, ask or give aid and spread the news of the Vesselwreck to others. If an accident occurs on board the skipper must be above board and record events such accidents in the logbook and reported to the harbor master. There are still many weaknesses of criminal responsibility in the corporation, among others: when the corporation is declared as a criminal, how the corporation is responsible, the types of sanctions what can be meted out to the corporation, not regulated penal substitute fines are not paid by the corporation and unregulated the offense to corporation. Because implementation guidelines in the draft penal Code there is renewal in the subject field of the offense and criminal liability system.Keywords: Commercial Vessels; Skipper; Criminal Liability.